The longitudinal association between onion consumption and risk of depressive symptoms: results from the TCLSIH Cohort study and the UK Biobank. Issue 1 (8th December 2022) - Yang, Honghao; Gu, Yeqing; Zhang, Bei; Meng, Ge; Zhang, Qing; Liu, Li; Wu, Hongmei; Zhang, Shunming; Zhang, Tingjing; Wang, Xuena; Zhang, Juanjuan; Sun, Shaomei; et al.
Abstract : Two large prospective cohorts from China and the UK have firstly demonstrated that habitual onion consumption was associated with a lower risk of depressive symptoms in the general population. Abstract : Background and aims : Onions have shown antidepressant effects but relevant evidence from people was limited. Thus, we aimed to explore the prospective association between onion consumption and risk of depressive symptoms in the general population. Methods : We used data from 2 cohorts: the Tianjin Chronic Low-grade Systemic Inflammation and Health (TCLSIH) cohort included 7739 participants (males, 57.6%) with a mean age of 39.5 years, and the UK Biobank included 169 806 individuals (males, 45.2%) with a mean age of 55.7 years. In the TCLSIH cohort, onion consumption was assessed by a validated food frequency questionnaire from May 2013; depressive symptoms were evaluated by the Chinese version of the Self-Rating Depression Scale (SDS scores ≥ 45) and were assessed up to 2018. In the UK Biobank, onion consumption was measured by 1–5 times validated 24-hour dietary recalls in 2006–2010; depressive symptoms were determined through the linked hospital records and death registries and were assessed up to 2018. Multivariable Cox proportional hazards models were employed to determine the association between onion consumption and risk of depressive symptoms. Results : A total of 1098 and 1924 cases of depressive symptoms were identified during 15 004 person-years and 1 243 832 person-years of follow-up in the TCLSIH cohort and the UK Biobank, respectively. After adjusting for many confounding factors, the fully adjusted HRs (95% CI) of depressive symptoms comparing the higher levels to the lowest level of onion consumption were 0.78 (0.65, 0.94), 0.73 (0.61, 0.87), and 0.77 (0.64, 0.92) in the TCLSIH cohort ( p for trend = 0.01); and were 0.79 (0.68, 0.93), 0.81 (0.69, 0.94), and 0.97 (0.85, 1.12) in the UK Biobank ( p for trend = 0.07). Similar associations were observed in the sensitivity analyses. Conclusion : Our results indicated that habitual onion consumption was associated with a lower risk of depressive symptoms in two cohorts. However, this association was not statistically significant in the highest level of onion consumption in the UK Biobank.